Transparency and credibility of industry-sponsored clinical trial publications: a survey of journal editors. (3rd July 2019) - Mooney, LaVerne A.; Fay, Lorna; DeCastro, Barbara; Zanki, Tatjana A.; Mansi, Bernadette
Abstract: Objective: To examine how medical journal editors perceive changes in transparency and credibility of industry-sponsored clinical trial publications over a 5 year period (2010 to 2015). Methods: From July to September 2015, a survey link was emailed to journal editors identified from the Thomson Reuters registry. Editors ranked their perception of: a) change in transparency and credibility of industry-sponsored clinical trial publications; b) 8 "Publication Best Practices" and the impact of each on transparency; and c) the importance and adoption of the previously published "10 Recommendations for Closing the Credibility Gap in Reporting Industry-Sponsored Clinical Research". Results: Of 510 editors who opened the survey, the analysis pool comprised a total of 293 editors. The majority of respondents reported their location as the US (46%) or EU (45%) and most commonly reported editorial titles were deputy/assistant editor (36%), editor-in-chief (35%) and section editor (24%). More editors reported improved versus worsened transparency (63.5% vs. 6.1%) and credibility (53.2% vs. 10.4%). Best practices that contributed most to improved transparency were "disclosure of the study sponsor" and "registration and posting of trial results". Respondents ranked the importance of nine recommendations as moderate or extremely important, and adoption of all recommendations was ranked minimal to moderate. Conclusions: The 293 editors who responded perceived an improvement in the transparency and credibility of industry-sponsored publications from 2010 to 2015. Confirmation of the importance of 9/10 recommendations by the respondents was encouraging. Yet, low adoption rates suggest that additional work is required by all stakeholders to improve best practices, transparency and credibility.